Determinasi Audit Judgment : Kajian Empiris pada KAP Wilayah Jakarta Selatan - Dewi Rejeki (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research was conducted to determine the partial or simultaneous effect of Auditor Expertise, Compliance Pressure and Independence on Audit Judgment at Public Accounting Firms in the South Jakarta Region. This research was conducted at the Public Accounting Firm (KAP) in the South Jakarta Region. The data analysis technique in this study is to use quantitative methods and use primary data. The data collection method used in this research is a survey method of Public Accounting Firms in the South Jakarta Region. The method of determining the sample of this study uses purposive sampling. 50 research respondents consist of Senior Auditors, Supervisors, Managers who work in Public Accounting Firms in the South Jakarta Region. This study was tested by multiple regression analysis using the SPSS program. The results showed that Auditor Expertise, Compliance Pressure and Independence either partially or simultaneously have a positive influence on Audit Judgment.